Food Innovation of Sundanese Nasi Liwet, How New Formulation and Brand Advertise New Food Product - Pinandoyo, Dimas Bayu; Khubber, Sucheta (Politeknik Negeri Media Kreatif, 2023)
Sundanese Nasi Liwet have less acceptance especially in consumers. Innovation was conducted to improve the consumers and markets acceptance of Sundanese Nasi Liwet. Innovation was adopting fusion method, while branding was changed by branding new innovated product with “Kubu Liwet”. The new product had yellow color made with original recipe. The condiment was crispy fried chicken skin and stir-fried chayote. Topping that being used was sambal matah. Open sensory evaluation and marketing test was conducted to measure the success rate of advertisement by formulation and branding. Open sensory evaluation was conducted toward 100 consumers in Bogor City. Sensory evaluation conducted by applying level 5 Likert scale. Market acceptance conducted by measuring average daily sell point of product during 6-week market time. Overall acceptability improved from 3.62/5 to 4.33/5. Average daily selling product of original Nasi Liwet was 6.4 while innovated product was 13.4. It was found that the new formulation and brand successfully advertise the new innovated Sundanese Nasi Liwet.